2017
DOI: 10.1021/acs.inorgchem.7b01653
|View full text |Cite
|
Sign up to set email alerts
|

Identification of α-Fe in High-Silica Zeolites on the Basis of ab Initio Electronic Structure Calculations

Abstract: α-Fe is the precursor of the reactive Fe═O core responsible for methane oxidation in Fe-containing zeolites. To get more insight into the nature and stability of α-Fe in different zeolites, the binding of Fe(II) at six-membered-ring cation exchange sites (6MR) in ZSM-5, zeolite beta, and ferrierite was investigated using DFT and multireference ab initio methods (CASSCF/CASPT2). CASPT2 ligand field (LF) excitation energies of all sites were compared with the experimental DR-UV-vis spectra reported by Snyder et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Moving up in Fe loading from the single-site -Fe materials, Fe spectators appear in the UV-Vis and Mössbauer spectra of Fe-*BEA. 31 These are likely monomers in the other exchange sites of the zeolite, as calculated by Hallaert et al 44 Their exact coordination environment should be confirmed with site selective techniques (VTVH-MCD, rR). While these may be less relevant for catalysis, taking a step back to figure out the less glamorous spectroscopy will pay off eventually as they will likely cloud the spectroscopy of dimers that should start forming upwards a certain Fe/Al ratio.…”
Section: Probing Other Monomeric and Dimeric Fe Sites In Zeolitesmentioning
confidence: 69%
See 2 more Smart Citations
“…Moving up in Fe loading from the single-site -Fe materials, Fe spectators appear in the UV-Vis and Mössbauer spectra of Fe-*BEA. 31 These are likely monomers in the other exchange sites of the zeolite, as calculated by Hallaert et al 44 Their exact coordination environment should be confirmed with site selective techniques (VTVH-MCD, rR). While these may be less relevant for catalysis, taking a step back to figure out the less glamorous spectroscopy will pay off eventually as they will likely cloud the spectroscopy of dimers that should start forming upwards a certain Fe/Al ratio.…”
Section: Probing Other Monomeric and Dimeric Fe Sites In Zeolitesmentioning
confidence: 69%
“…With a limited number of boundary conditions set by experiment, modelling at sufficiently high levels of theory can provide quite accurate predictions on active site geometry and electronic structure. 44 Between a restricted number of possible configurations, the condition dependence of different Fe species' stability in zeolites can also be predicted with reasonable confidence. 45 The information from these studies, whether relevant to -Fe/-O or not, may give useful insight in Fe sites for catalysis when they become experimentally defined in the future.…”
Section: Three Decades Uncovering the -Fe/-o Sitesmentioning
confidence: 79%
See 1 more Smart Citation
“…The α‐site is a planar 6MR along the straight channel with an O−T−O bridge, while the β‐site is a planar 6MR in the perpendicular channel. These sites have also been identified in the MFI framework . The γ‐site is boat‐shaped with one O−T−O bridge and is found in the intersection of the straight and perpendicular channels.…”
Section: Direct Ch4 To Ch3oh Conversion Over Zeolitesmentioning
confidence: 98%
“…27 Moreover, the near exclusive presence of only the active α-Fe II species was noted at low iron loadings using Mössbauer spectroscopy while at higher loadings, other undesired iron species (spectators) are formed. 26,28 As a consequence, further improvement in the productivity in MPO will benefit from control over the Al-distribution of the host zeolite (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%